Species That Fly at a Higher Game: Patterns of Deep–Water Emergence Along the Chilean Coast, Including a Global Review of the Phenomenon - Häussermann, Vreni; Ballyram, Stacy Anushka; Försterra, Günter; Cornejo, Claudio; Ibáñez, Christian M.; Sellanes, Javier; Thomasberger, Aris; Espinoza, Juan Pablo; Beaujot, Francine (Frontiers in Marine Science, 2021)
Deep-water emergence describes the phenomenon of species commonly known from greater depth (below 200 m), locally occurring in significantly shallower water (euphotic zone, mostly shallower than 50 m). Although the phenomenon is mentioned and deep-water emergent species have been described from the fjord regions of North America (Alaska and British Columbia), Scandinavia (Norway and Sweden) and New Zealand, local or global hypotheses to explain this phenomenon have rarely been tested. This publication includes the first literature review on deep-water emergence. Our knowledge of distribution patterns of Chilean marine invertebrates is still very scarce, especially from habitats below SCUBA diving depth. In our databases, we have been gathering occurrence data of more than 1000 invertebrate species along the Chilean coast, both from own research and from the literature. We also distributed a list of 50 common and easily in-situ-identifiable species among biologically experienced sport divers along the Chilean coast and recorded their sighting reports. Among others, the analysis of the data revealed patterns from 28 species and six genera with similar and particularly combined longitudinal and bathymetric distribution along the entire Chilean coast: in Central and Northern Chile (19°S-39°S) these species are normally restricted to deep water (> 200m) but are common to locally abundant in diving depth (< 30m) in Chilean Patagonia (>39°S-56°S), with 28 species being present in shallow water of North Patagonia, 32 in Central Patagonia and 11 in South Patagonia. The species belong to the phyla Cnidaria (five species, four genera), Mollusca (five species, two genera), Arthropoda (two species) and Echinodermata (17 species). We ran several analyses comparing depth distribution between biogeographic regions (two-way ANOVA) and comparing abiotic parameters of shallow and deep sites to search for correlations of distribution with environmental variables (Generalized Linear Models). For the analyses, we used a total of 3328 presence points and 10635 absence points. The results of the statistical analysis of the used parameters, however, did not reveal conclusive results. We summarize cases from other fjord regions and discuss hypotheses of deep-water emergence from the literature for Chilean Patagonia.